Are 2-Year Colleges the Key? Institutional Variation and the Gender Gap in Undergraduate STEM Degrees. (4th March 2019) - Perez-Felkner, Lara; Thomas, Kirby; Nix, Samantha; Hopkins, Jordan; D'Sa, Mitchell
ABSTRACT: Studies of gender gaps in science, technology, engineering, and mathematics (STEM) higher education have rarely considered 2-year colleges, despite the fact that most enrollees are women. Situated in an interdisciplinary literature on gender and inequality in students' pathways to STEM higher education, this study used Beginning Postsecondary Students:2004/2009 nationally representative panel data on 5, 210 undergraduate students. The primary research question posed was: How does initial college type influence the gender gap in STEM undergraduate degrees? First, we describe and illustrate distinct patterns in the degrees earned by men and women who initially enroll in 2-year and 4-year institutions. Leveraging rich control measures, we estimated a series of multivariate logistic regressions to robustly estimate gender gaps in non-STEM, social/behavioral sciences, life sciences, and natural/engineering sciences degree fields. Results from these degree clusters were distinct and underscored the limitations of "STEM" as an umbrella category. College type was more influential on the life sciences and social/behavioral sciences; effects on natural/engineering sciences degrees were experienced primarily by men, especially among baccalaureate degree earners. Gender gaps among life sciences and natural/engineering sciences bachelor's degree earners were wider among initial 2-year students (favoring women and men, respectively). The discussion contextualizes and offers implications from our findings.